High capacity packet switching with a soliton pulse in a nonlinear micro ring resonator - Mitatha, S.; Dejhan, K.; Thongmee, S.; Yupapin, P. P. (My University, 2008)
We propose a new design of the secured packet switching using the nonlinear behaviors of soliton in a micro ring resonator, where the nonlinear penalty of light traveling in the device becomes benefit. The chaotic signals are generated by a Kerr effects nonlinear type of soliton in a micro ring resonator, where the control input power can be used to specify the output filtering signals. Some device parameters are chosen and simulated using the proposed model. Results obtained have shown in good agreement with the practical device behaviors. The potential of using such a device for communication security is performed and discussed. For instance, the packet switching of the chaotic encoding data increases from the chaotic signal encoding of 100 bit/s. Results obtained have shown the potential of using such a proposed device for the tunable bandpass and band-stop filters, in which the packet switching data can be performed and secured. © 2008 Trans Tech Publications, Switzerland.
Keywords: Nonlinear ring resonator; Packet switching; Soliton switching